Enhanced intestinal glucose and alanine transport in cystic fibrosis. Issue 7 (July 1990) - Baxter, P; Goldhill, J; Hardcastle, J; Hardcastle, P T; Taylor, C J
Abstract : The rise in short-circuit current associated with the active transport of glucose and alanine was measured in intestinal biopsy samples from children with cystic fibrosis. The glucose-induced increase in the short-circuit current was greater in the cystic fibrosis tissues than in control samples over the whole range of concentrations tested (2.5-35 mM), a reflection of an increased maximum rate of transport. Similar results were obtained with alanine. These findings suggest that active Na(+)-linked nutrient transport is enhanced in cystic fibrosis.